Pemanfaatan Senyawa Antosianin pada Ekstrak Bunga Rosella (Hibiscus sabdariffah) Sebagai Pendeteksi Alami Formalin pada Tahu - Nisa, Indana Faiza; Nadifah, Umi; Mentari, Ayu (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Nisa, I. F., Nadifah, U., Mentari, A. (2024). Utilization of anthocyanin compound in rosella flower extract (Hibiscus sabdariffah) as a natural formalin detector in tofu. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp.255–261). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Rosella (Hibiscus sabdariffah) is one of the herbal plants that contains anthocyanin compounds and can react with formalin which is acidic, causing significant color changes. This study aimed to utilize anthocyanin compounds in rosella flower extract as a natural detector of formalin content in tofu. To achieve this goal, this study used an experimental method with a qualitative approach. Tofu samples were obtained from several traders in the market around Teluk Gelam Subdistrict, Ogan Komering Ilir Regency. Preparation of rosella flower extract was carried out using maceration method with 70% ethanol solvent. The rosella flower extract was then dripped on tofu samples and observed for color changes. The observation data were analyzed descriptively qualitative. The results showed that rosella flower extract was effective in detecting formalin content in tofu. The best treatment was obtained at a concentration of 5 ml rosella extract + 20 ml distilled water (P3) which produced a clear color change in the tofu. Tofu containing formalin will change color to a solid red, while tofu that does not contain formalin does not show significant color changes. Thus, rosella flower extract can be utilized as a natural detector of formalin content in tofu.